Therapeutic Potentials of Antiviral Plants Used in Traditional African Medicine With COVID-19 in Focus: A Nigerian Perspective - Attah, Alfred Francis; Fagbemi, Adeshola Adebayo; Olubiyi, Olujide; Dada-Adegbola, Hannah; Oluwadotun, Akinseinde; Elujoba, Anthony; Babalola, Chinedum Peace (Frontiers in Pharmacology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic is caused by an infectious novel strain of coronavirus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which was earlier referred to as 2019-nCoV. The respiratory disease is the most consequential global public health crises of the 21st century whose level of negative impact increasingly experienced globally has not been recorded since World War II. As of August 14, 2020, the WHO reported a growing effect of COVID-19 with 20,730,456 laboratory-confirmed cases and 751,154 deaths, reported to WHO from different countries of the World. Up till now, there has been no specific globally authorized anti-viral drug, vaccines, supplement or herbal remedy available for the treatment of this lethal disease except preventive measures, supportive care and non-specific treatment options adopted in different countries via divergent approaches to halt the pandemic. However, many of these interventions have been documented to show some level of success particularly the Traditional Chinese Medicines while there is a paucity of well-reported studies on the impact of the widely embraced Traditional African Medicines (TAM) adopted so far for the prevention, management and treatment of COVID-19. We carried out a detailed review of publicly available data, information and claims on the potentials of indigenous plants used in Sub-Saharan Africa as antiviral remedies with potentials for the prevention and management of COVID-19. In this review, we have provided a holistic report on evidence-based antiviral and promising anti-SARS-CoV-2 properties of African medicinal plants based on in silico evidence, in vitro assays and in vivo experiments alongside the available data on their mechanistic pharmacology. In addition, we have unveiled knowledge gaps, provided an update on the effort of the African Scientific community towards demystifying the dreadful SARS-CoV-2 micro-enemy of man and have documented popular anti-COVID-19 herbal claims emanating from the continent for the management of COVID-19 while the risk potentials of herb-drug interaction of antiviral phytomedicines, when used in combination with orthodox drugs, have also been highlighted. This review exercise may lend enough credence to the potential value of African medicinal plants as possible leads in anti-COVID-19 drug discovery through research and development.